Survival analysis of time to uptake of modern contraceptives among sexually active women of reproductive age in Nigeria (2015)
Objective: To assess the timing of modern contraceptive uptake among married and never-married women in Nigeria. Design: A retrospective cross-sectional study. Data and method: We used nationally representative 2013 Demographic and Health Survey data in Nigeria. Modern contraceptive uptake time was measured as the period between first sexual intercourse and first use of a modern contraceptive. Non-users of modern contraceptives were censored on the date of the survey. Kaplan–Meier survival curves were used to determine the rate of uptake. A Cox proportional hazards model was used to determine variables influencing the uptake at 5% significance level. Participants: A total of 33 223 sexually active women of reproductive age. Outcome measure: Time of uptake of a modern contraceptive after first sexual intercourse. Results: The median modern contraceptive uptake time was 4 years in never-married and 14 years among ever-married women. Significant differences in modern contraceptive uptake existed in respondents’ age, location, education and wealth status. Never-married women were about three times more likely to use a modern contraceptive than ever-married women (aHR=3.24 (95% CI 2.82 to 3.65)). Women with higher education were six times more likely to use a modern contraceptive than those without education (aHR=6.18 (95% CI 5.15 to 7.42)). Conclusions: The rate of modern contraceptive uptake is low, and timing of contraceptive uptake during or after first sexual intercourse differed according to marital status. Age and number of children ever born influenced modern contraceptive uptake among the never-married women, but religion and place of residence were associated with the probability of modern contraceptive uptake among ever-married women.